Peat Water Treatment Using Modified Red mud - Ivontianti, Wivina Diah; Shalindry, Riysan Octy; Maleiva, Lalak Tarbiyatun Nasyin (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Red mud is an alumina refinery waste residue that has been used to develop an effective adsorbent for wastewater treatment, one of which can be applied to peat water. Peat water treatment is carried out using the adsorption method. This study sought to ascertain the impact of the acid types of acid HCl and H2SO4 solution on dealumination process to the characteristics of the red mud adsorbent based on the analysis of XRF and BET instruments. In addition, this study was to determine the effect of the effect of mass variations of the red mud adsorbent on the effectiveness of peat water treatment. This research was conducted on a laboratory scale using variations in the adsorbent mass of 1 g; 3 g ; 5 g and 7 g and variation of contact time used was 15, 30, 60, and 90 minutes . The results showed an increase in the Si/Al ratio from 1.064% to 1.697% for HCl, while for H2SO41.565%. Increasing of surface area with HCl was 179.574% while using H2SO4 was 162.891%. The results of research on the adsorption process with variations in the mass of the adsorbent 1, 3, 5, and 7 grams obtained the results of peat water pH respectively were 6.6; 7.0; 7.0; and 7,1. In the Fe metal there were removal of 73.39%; 37.09%; 24.19% and -141.93%. Then for the organic matter removal efficiency were 53.07%; 50%; 44.30% and -17.98% respectively. In variation of contact time for the parameter Fe, there were removals of 29,03%, 27,41%, and 24,19% respectively. Then for organic matter the removal efficiencies were 32,46%, 54,82%, 48,25%, and 44,29%. The optimum condition based on the result obtained are the 5 g for the mass adsorbent and 30 minute for contact time. Keywords: adsorbent; dealumination; H2SO4; HCl; peat water; red mud.